Physics Characteristics of Canarium Oil with Variations in Drying Methods - Savira Maba; Helen C D Tuhumury; Vita N Lawalata (Universitas Pattimura, 2022)
The goal of this study was to investigate the physic properties of canarium oil using various drying methods. This study used a randomized block design with three drying methods: sun drying (3 days), roasting dying (80°C for 1 hour), and oven dying (70°C for 1 hour) with two replications. The refractive index, specific gravity, yield of canarium oil were all measured. The results showed that canarium oil has a refractive index of 1.414-1.415, a specific gravity of 0.941-0.943 g/cm3,, a yield of 9.23-11.30%.